Recordando la parotiditis en la era del SARS-CoV-2 - Salgueiro-Marques, A (2021)
New 2019-Coronavirus (SARS-CoV-2) pandemic is presenting daily diagnostic challenges to emergency departments (ED) doctors, especially as an increasing number of atypical clinical presentations have been reported, including acute sialadenitis (most of parotid). We present a case of a 46-year-old obese caucasian woman, with no relevant medical history, that presented in ED with complaints suggesting parotitis, with normal laboratory tests, at first with no virus isolation, confirmed by computed tomography. One week later, anosmia and dysgeusia were notice, and SARS-CoV-2 was tested and confirmed. Authors want to alert that SARS-CoV-2 should be excluded as parotitis etiology, highly important, especially in this pandemic phase, as a way of transmission contro